2020
DOI: 10.1097/md.0000000000019904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photobiomodulation in Children with Down Syndrome and Possible Sleep Bruxism: Protocol For A Randomized, Controlled, Blind, Clinical Trial

Abstract: Hypotonia, particularly of the masticatory and oropharyngeal muscles, is 1 of the main characteristics of Down Syndrome (DS), resulting in impaired speech, chewing and swallowing. Moreover, the complete or partial obstruction of the airways during sleep may occur due to hypotonia of the tongue, leading to snoring and sleep disorders, such as obstructive apnea and sleep bruxism. Objective: Analyze salivary levels of dopamine and cortisol and muscle activity before and after treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
0
9
0
5
Order By: Relevance
“…Mostafavi et al [35] Oral administration of hydroxyzine A. Ghanizadeh [36] Photobiomodulation M.C.C. Salgueiro et al [37] Orthodontic treatment (rapid palatal expansion) A. Bellerive et al [33] Another therapy proposed for reducing bruxism in children is physiotherapy. The "self-awareness of movement" concept was put forth to improve the organization and coordination of body movements [6].…”
Section: Treatment Methods Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mostafavi et al [35] Oral administration of hydroxyzine A. Ghanizadeh [36] Photobiomodulation M.C.C. Salgueiro et al [37] Orthodontic treatment (rapid palatal expansion) A. Bellerive et al [33] Another therapy proposed for reducing bruxism in children is physiotherapy. The "self-awareness of movement" concept was put forth to improve the organization and coordination of body movements [6].…”
Section: Treatment Methods Authorsmentioning
confidence: 99%
“…In children, acupoint stimulation with laser is recommended because it is painless and requires a shorter exposure time [34]. In addition, photobiomodulation was used in children with Down syndrome in a study by Salgueiro et al which showed that acupuncture point treatment relieved the symptoms of bruxism in these children and reduced the levels of cortisol [37,38].…”
Section: Treatment Methods Authorsmentioning
confidence: 99%
“…A protocol proposal for a randomized, controlled, blind, clinical trial for the treatment of SB in children with DS has been recently published [ 70 ]. Underlying this protocol, there are studies on acupuncture, a technique successfully used for the treatment of bruxism, obtaining a reduction in the activity of the masseter and anterior temporal muscles and an anxiety reduction as well [ 71 ].…”
Section: Managementmentioning
confidence: 99%
“…Generalized orofacial muscles hypotonia e.g., orbicularis oris, zygomatic, masseter, and temporalis muscles, contributes to poor oral seal, poor suck, weak tongue control, and problems with jaw stability. This may result in impairments to speech, swallowing, and mastication in these individuals [ 5 , 6 ]. Hypotonia, muscle weakness, sluggish motor responses, and sensory changes can reduce their ability to maintain proper muscle balance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may result in impairments to speech, swallowing, and mastication in these individuals [ 5 , 6 ]. Hypotonia, muscle weakness, sluggish motor responses, and sensory changes can reduce their ability to maintain proper muscle balance [ 5 ]. Other general manifestations found in subjects with DS are stunted growth, congenital heart defects, thyroid dysfunction, brachycephaly, upper airway obstruction, respiratory breathing disorders, severely inhibited sagittal development in the midface region, reduced size of maxillary and mandibular bones, breathing through the mouth, risk of aspiration pneumonia, and a weak immune system [ 2 ].…”
Section: Introductionmentioning
confidence: 99%